2010
DOI: 10.1159/000287351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracellular ATP on Cisplatin-Induced Cytotoxicity in Human Ovarian Carcinoma Cells

Abstract: Background: Cisplatin resistance has been mainly associated with decreased cellular accumulation and increased intracellular glutathione (GSH) levels. ATP is known to increase the membrane permeability of cells and to decrease intracellular GSH levels. Our study aimed at using extracellular ATP to sensitize ovarian carcinoma cells towards cisplatin. Methods: The MTT assay was used to determine the EC50 of cisplatin in the human ovarian carcinoma cell line A2780 and its cisplatin-resistant variant A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Variants of the RB1 gene have been implicated as risk factors for invasive ovarian cancer [429]. A recent study has shown that the presence of ATP during the treatment of human ovarian carcinoma with cisplatin leads to additive cytotoxicity [430].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Variants of the RB1 gene have been implicated as risk factors for invasive ovarian cancer [429]. A recent study has shown that the presence of ATP during the treatment of human ovarian carcinoma with cisplatin leads to additive cytotoxicity [430].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…This suggested us that cinobufacini could enhance killing effect of osteosarcoma cells when combined with cisplatin, therefore, a greater anti-tumor effect would be triggered if cinabufotalin were used in the chemotherapy. Since there were a great number reports about side effects on digestive, nervous, blood and other body systems due to application of cisplatin during the regular chemotherapy of osteosarcoma patients (Konstantakou et al, 2009;LaPensee et al, 2010;Maroto et al, 2011;Rotte et al, 2010;Sprowl et al, 2012), we suppose ,combination of cinobufacini and cisplatin will avoid all these side effects of chemotherapy, and by this way, cinobufacini will promote from the second-line to the first-line anti-tumor drugs and will play a more important role in osteosarcoma therapy. In addition, our research showed the killing effect by the application of cinobufotalin and cisplatin were fulfilled by inducing apoptosis of osteosarcoma cells which were revealed from the cell morphology (Figure2A-2D), cell apoptosis (Figure2E -2H) and FCM analysis (Figure3A-3B).…”
Section: Discussionmentioning
confidence: 99%
“…However, the recurrences in those patients who were found with stable or progressive RCB after IDS were mainly drug-resistant recurrences, so the chemotherapy plans may be changed after IDS. In order to improve prognosis after IDS, fresh tissue or cells may be used to assay drug resistance in vitro to help make individual chemotherapy decisions [23]. For patients with clinical benefit as evaluated by serum CA-125, whose RCB decreased no more than 50%, the recurrence type may be of the sensitive or partially platinum-sensitive type.…”
Section: Discussionmentioning
confidence: 99%